Проблемы продления ресурса строительных конструкций - Слюсаренко, Ю.С.; Любченко, И.Г.; Кривошеев, П.И. (Автоматическая сварка, 2008)
The paper deals with the problems of development of normative-legal base for life assurance of constructions and
development of methods for assessment of the life of structures, buildings and constructions taking into account the
physico-mechanical properties of materials, technogenous and natural effects.